The Quota Policy in Portugal: The Role of Political Parties and State Feminism. RCCS Annual Review - Monteiro, Rosa (2013)
The so-called Parity Act was an important milestone in the promotion of gender equality in Portugal, due, amongst other things, to its impact upon an electoral system that the inertia of the party political system had been unable to change. Analyses of the appearance of quota policies in Portugal have not generally considered the role played by the main official body for equality, the Commission for Citizenship and Gender Equality, and its networks. However, as Mona Lena Krook has pointed out, efforts to increase the number of women in political office have rarely occurred without the mobilization of women. This paper adopts the state feminism approach to explore the Commission’s decisive role in presenting feminist claims before the state (a role that has been systematically ignored), focusing on the way this body as well as the women’s associations related to it have contributed to promote women’s participation in politics in Portugal.